Boat lutes in the Visayas and Luzon traces of a lost tradition - Brandeis, Hans (Musika Jornal, 2012)
The Spanish guitar is the most popular instrument in the Philippines today. But centuries before the arrival of the Spaniards it already had Asian prototypes on the numerous islands of the archipelago: long-necked lutes in many regional variations. This can be assumed on one hand from the wide variety of lute types still existing in Mindanao and Palawan today, at least 23 lute types used by at least 35 ethnic groups, and on the other hand from the occurrence of indigenous terms for these boat lutes in the language of those regions, where no boat lutes can be found anymore, namely on the main island of Luzon in the northern Philippines and on the Visayan islands of the Central Philippines. However, no one can be sure if the same name for a boat lute in two different regions could mean the same instrument, a similar instrument or a totally different instrument at that.